Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Promosi Terhadap Keputusan Pembelian Di Sushi Hiro Kelapa Gading - Shisilia, Shasa; Efiani, Efiani (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to analyze the impact of product quality, service quality and promposion on customer satisfaction on Sushi hiro kelapa gading. The population in the study was consumers who visited Sushi hiro kelapa ivory and sample data was taken as many as 385 respondents which was carried out with the Accidental Sampling Technique in the study including multiple linear regression tests, the methods carried out in this study include classical assumption tests, namely normality tests, heteroscedasticity tests, multicollinearity tests, and linearity tests, in addition to data hypotheses were also tested using the f test and t test. From this study, it was concluded in the multiple linear regression analysis test that product quality, service quality, and promotion have an effect both partially and simultaneously on customer satisfaction.